Green synthesis and characterization of gelatin-based and sugar-reduced silver nanoparticles. - Darroudi, Majid; Ahmad, M.B.; Abdullah, A.H.; Ibrahim, N.A. (Dove Medical Press, 2011)
Silver nanoparticles (Ag-NPs) have been successfully prepared with simple and "green" synthesis method by reducing Ag + ions in aqueous gelatin media with and in the absence of glucose as a reducing agent. In this study, gelatin was used for the first time as a reducing and stabilizing agent. The effect of temperature on particle size of Ag-NPs was also studied. It was found that with increasing temperature the size of nanoparticles is decreased. It was found that the particle size of Ag-NPs obtained in gelatin solutions is smaller than in gelatin-glucose solutions, which can be related to the rate of reduction reaction. X-ray diffraction, ultravioletvisible spectra, transmission electron microscopy, and atomic force microscopy revealed the formation of monodispersed Ag-NPs with a narrow particle size distribution.